1997
DOI: 10.1002/jlb.62.6.805
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of human neutrophil inflammatory responses by nitric oxide: studies in unprimed and LPS-primed cells

Abstract: Because nitric oxide (NO) can act both as a regulatory and as a toxic molecule, we have studied N-formyl-methionyl-leucyl-phenylalanine (fMLF) -stimulated responses of human neutrophils (PMNs) during various conditions of NO modulation in unprimed and bacterial lipopolysaccharide (LPS) -primed cells. Effects of various NO modulators were assessed on stimulated superoxide (O2-) generation, granule exocytosis, homotypic aggregation, and rises in intracellular free Ca2+ ([Ca2+]i). Significant differences in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 0 publications
0
41
0
1
Order By: Relevance
“…Nitrite levels were measured as an index of NO generation in the culture supernatants, by a sensitive fluorimetric method of Misko et al [15], the details of which have been recently reported from our laboratory [16]. For optimal NO generation, PMN or EC were supplemented with L-arginine (200 µM).…”
Section: Nitrite Measurementsmentioning
confidence: 99%
“…Nitrite levels were measured as an index of NO generation in the culture supernatants, by a sensitive fluorimetric method of Misko et al [15], the details of which have been recently reported from our laboratory [16]. For optimal NO generation, PMN or EC were supplemented with L-arginine (200 µM).…”
Section: Nitrite Measurementsmentioning
confidence: 99%
“…We recently demonstrated that NO is involved in the candidacidal activity of rat inflammatory peritoneal neutrophils [15] and other authors have shown that NO contributes to the tumoricidal activity of those cells [16]. In addition, the NO-generating system in neutrophils has been suggested to function as an autocrine mechanism that may regulate PMN activation during various pathophysiological conditions in vivo [17]. Therefore, it is important to elucidate the modulatory mechanisms involved in the induction of the NOS pathway in neutrophils.…”
Section: Introductionmentioning
confidence: 97%
“…In Jurkat T-cells, long-term exposure to nitric oxide (NO) leads to activation of several MAP kinases, with ERK being the most responsive (21). LPS induces NO production in neutrophils, and this process is thought to mediate many of its inflammatory activities (22)(23)(24)(25)(26)(27). Stimulation of neutrophils with fMLF can also induce NO production, which is thought to play an important role in chemotaxis and degranulation elicited by this agent (28 -32).…”
mentioning
confidence: 99%